Sphingolipids and DHA Improve Cognitive Deficits in Aged Beagle Dogs - Araujo, Joseph A.; Segarra, Sergi; Mendes, Jessica; Paradis, Andrea; Brooks, Melissa; Thevarkunnel, Sandy; Milgram, Norton W. (Frontiers in Veterinary Science, 2022)
Canine cognitive dysfunction syndrome (CDS) is a disorder found in senior dogs that is typically defined by the development of specific behavioral signs which are attributed to pathological brain aging and no other medical causes. One way of objectively characterizing CDS is with the use of validated neuropsychological test batteries in aged Beagle dogs, which are a natural model of this condition. This study used a series of neuropsychological tests to evaluate the effectiveness of supplementation with a novel lipid extract containing porcine brain-derived sphingolipids (Biosfeen®) and docosahexaenoic acid (DHA) for attenuating cognitive deficits in aged Beagles. Two groups (n=12), balanced for baseline cognitive test performance, received a daily oral dose of either test supplement, or placebo over a six-month treatment phase. Cognitive function was evaluated using the following tasks: delayed non-matching to position (DNMP), selective attention, discrimination learning retention, discrimination reversal learning, and spatial discrimination acquisition and reversal learning. The effect of the supplement on brain metabolism using magnetic resonance spectroscopy (MRS) was also examined. A significant decline (p=0.02) in DNMP performance was seen in placebo-treated dogs, but not in dogs receiving the supplement, suggesting attenuation of working memory performance decline. Compared to placebo, the supplemented group also demonstrated significantly improved (p=0.01) performance on the most difficult pattern of the spatial discrimination task and on reversal learning of the same pattern (p=0.01), potentially reflecting improved spatial recognition and executive function, respectively. MRS revealed a significant increase (p=0.048) in frontal lobe glutamate and glutamine in the treatment group compared to placebo, indicating a physiological change which may be attributed to the supplement. Decreased levels of glutamate and glutamine have been correlated with cognitive decline, suggesting the observed increase in these metabolites might be linked to the positive cognitive effects found in the present study. Results of this study suggest the novel lipid extract may be beneficial for counteracting age-dependent deficits in Beagle dogs and supports further investigation into its use for treatment of CDS. Additionally, due to parallels between canine and human aging, these results might also have applicability for the use of the supplement in human cognitive health.